PERAN UMKM DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT PASCA PANDEMI COVID-19 PADA KAMPUNG LOGAM NGINGAS KECAMATAN WARU KABUPATEN SIDOARJO - Aria Setia Ningtiyas (PT. Habe Cendekia Utama, 2026)
The type of research conducted in this thesis, which is field research aimed at seeing the role of MSMEs in boosting the community's economy post-COVID-19 pandemic in Kampung Logam Ngingas, Waru District, Sidoarjo Regency. The data collection technique used in this thesis involves interviews with the owners and employees of metal MSMEs located in Kampung Logam Ngingas. To gather data for the ongoing research, this thesis also uses observation methodology to monitor the situation in the field. The data used in this thesis were obtained from official sites, including those of Waru District, Sidoarjo Regency, and the Central Bureau of Statistics (BPS). The conclusion obtained from the research in this thesis is that there is no significant change in both production output and input. Although experiencing a decline in revenue, the owners of Ngingas metal MSMEs offer metal machine servicing services and sell some of their assets to stay afloat and avoid bankruptcy. These Ngingas metal MSMEs also have a positive impact on the residents of Ngingas village, as many jobs are absorbed, thereby increasing the income of the local community. Although Ngingas metal MSMEs were affected by COVID-19, this did not cause some workers to lose their jobs. This is evidenced by a 1.8% decrease in poverty in that year from the total population.